Investigating Trust and Wage discrimination in China by Gift Exchange Model - Wu, Shi (2013)
This study conducts an economic experiment in the framework of gift exchange model. It aims to investigate trust and wage discrimination from Chinese labors. This investigation is systematically carried out based on two levels: on a hierarchy level and on a country level. They are respectively identified the intra-organizational trust between different hierarchies within company and the outer-organizational trust between different countries. On a hierarchy level, there are three main findings. First, the intra-organizational trust is a hierarchical trust with little fairness concern in nature, which is a systematic phenomenon in the overall companies. Second, among all the four hierarchies, two middle hierarchies more discriminate the lowest hierarchy, in which middle-line managers discriminate basic workers most, in terms of wage offers. The top hierarchy, however, trusts the lowest hierarchy most, which indicates the bosses’ appreciation to the efforts from the bottom tier. Two tiers of managers well trust with each other. Third, reciprocity does not prevail among Chinese staffs due to the consensus of disvaluing employees. On a country level, there are four main findings. First, in Chinese labors’ opinion, Chinese employees is more trustworthy in most cases, but the most trustworthy employees are German and American who are the White people. The most wage-discriminated employees are Indian and African. Therefore, the ethnic factor influences trust and wage attitudes. However, it has only partially impact. So does ‘in-group favoritism’. The decisive factor is the economic factor. Finally, the geographic factor has no impact at all.